Wheat responses to stresses caused by low light intensity and water excess in the soil. Part II - Field Testing - Scheeren, Pedro Luiz; de Carvalho, Fernando Irajá Félix; Federizzi, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 1995)
The experiment was carried out in the field at the Agronomic Experimental Station of the Federal University of Rio Grande do Sul, in Brazil. The objective of this work was to assess the effect of stresses caused by water excess in the soil and by light reduction on 12 wheat (Triticum aestivum L.) genotypes. It was observed that the stress caused by shading, with 40% light reduction, caused significant modifications in agronomically important characters, like plant stature, number of fertile tillers per plant, peduncle length, number of fertile spikelets per spike, maximum number of grains per spikelet, plant weight and grain weight per plant; moreover, it increased the number of sterile spikelets per spike. The reductions caused by water excess in the soil were less significant to wheat as compared to the ones caused by shading, mainly as a result of environment conditions over cropping period.